2018
DOI: 10.1111/ppe.12500
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine‐preventable severe morbidity and mortality caused by meningococcus and pneumococcus: A population‐based study in France

Abstract: Mortality and morbidity rates related to vaccine-preventable meningococcal or pneumococcal infection could be reduced by one quarter with better implementation of immunisation programs. Such information could help enhance the perception of vaccine benefits and fight vaccine hesitancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…A mandatory immunization program is critical to protect infants against potentially life-threatening infections, and its schedule needs to be carefully respected (1), especially for the priming doses (2,3). Experts consider that any delay in these priming doses is dangerous for the infant, whereas a delay of 1 or 2 months may be relativized for boosters (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…A mandatory immunization program is critical to protect infants against potentially life-threatening infections, and its schedule needs to be carefully respected (1), especially for the priming doses (2,3). Experts consider that any delay in these priming doses is dangerous for the infant, whereas a delay of 1 or 2 months may be relativized for boosters (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…They described vaccines as safe and effective drugs. Numerous scientific studies corroborated their statements (23,24).…”
Section: Discussionmentioning
confidence: 65%
“…Unfortunately, we had demonstrated that lack of on-time vaccination was highly prevalent in this population. 28 Finally, an important point of this finding was that the primary outcome of future studies assessing the impact of care on child outcome should not be a composite of mortality and morbidity because this could lead to the loss of any significant association. 5,54 Analyses of the determinants of the quality of care allowed us to identify several possible targets for corrective action.…”
Section: Discussionmentioning
confidence: 99%